FOODTECH – A MODERN VECTOR IN THE DEVELOPMENT OF THE FOOD INDUSTRY - Ya. Yu. Chernikov (Вестник университета)
The article considers the current trends in the development of the food industry and the direction of food technology, which are based on the integration of digital technologies within the entire food chain: from farms and food production to packaging, storage, preparation and disposal of food. The purpose of this scientific paper is to study global trends, the growth rate of investments in this area and the prospects for the future. The author considers in more detail the Russian market for the delivery of ready-made rations, which is now gaining more and more popularity. The main drivers of the market are: new family values, health and nutrition standards, information technologies and the birth of new types of consumers. Only two serious competitors are currently represented in the Russian market: GrowFood and Performance Group, each with a market share of about 40 %. In the near future, a complete monopolization of the Russian market is possible, and this, of course, is a negative factor for consumers. The research area is in the early stages of the life cycle, and requires more attention and protection from institutional authorities.